KNOWLEDGE AND PRACTICE OF POSSIBLE AYURVEDIC, SIDDHA AND HOMEOPATHIC REGIMENS AGAINST NOVEL CORONA VIRUS PANDEMIC AMONG HEALTHCARE WORKERS: A CROSS-SECTIONAL STUDY - Premnath Parvathy,; V S. Aiswariya,; P. Abinaya,; Thomas Aiswarya,; B. Hariharasudan,; Abdullah Zoha, (International Journal of Ayurveda and Pharma Research, 2021)
Background: In the light of the pandemic COVID 19, world’s attention has turned to the immune system and body’s defense force. Identification of the level of epidemic preparedness and understanding of Ayurvedic, Homeopathic and Siddha regimens among health care workers is required to utilize their services in main stream health care effectively.Aim: The aim of this study to access the knowledge and practices of possible Ayurvedic, Homeopathic and Siddha regimens during novel corona virus pandemic.Materials and methods: A cross-sectional survey was undertaken among the health care workers with the help of 15 close ended questions. The one out of six-knowledge question were scored and analysed to identify differences with sociodemographic variables (age and occupation). Response to the three out of five questions on practices were analysed to Identify the differences, differing significantly in both knowledge and practice score.Result: Out of 286 responses, knowledge score significantly differed with age (P-value 0.04) and occupation (P-value 0.01). Practice scores significantly differed with age (P-value 0.01) and occupation (P-value 0.00). Our study shows that 70% of study population is aware of the medicinal properties of Neem, Tulsi and Ashwagandha against COVID 19 and 65% strongly believes the immune boosting effect of Vitamin C and 77% include citrus fruits in their diet.Conclusion: Adopting prophylactic and therapeutic strategies on the basis of Ayurveda, Homeopathy and Siddha are useful to the mankind in fighting against the COVID 19.